2017 Second International Conference on Fog and Mobile Edge Computing (FMEC) 2017
DOI: 10.1109/fmec.2017.7946419
|View full text |Cite
|
Sign up to set email alerts
|

A service orchestration architecture for Fog-enabled infrastructures

Abstract: The development of Fog Computing technology is crucial to address the challenges to come with the mass adoption of Internet Of Things technology, where the generation of data tends to grow at an unprecedented pace. The technology brings computing power to the surrounds of devices, to offer local processing, filtering, storage and analysis of data and control over actuators. Orchestration is a requirement of Fog Computing technology to deliver services, based on the composition of microservices. It must take in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 3 publications
0
43
0
2
Order By: Relevance
“…We refer to these dynamic and transient cells and colonies as fluid distributed organisations. A fog node can start autonomously, and become the lead orchestrator or part of a set of distributed orchestrators reaching some quorum before making decisions and dynamically leave the colony without warning [48].…”
Section: Edge and Fog Computingmentioning
confidence: 99%
See 2 more Smart Citations
“…We refer to these dynamic and transient cells and colonies as fluid distributed organisations. A fog node can start autonomously, and become the lead orchestrator or part of a set of distributed orchestrators reaching some quorum before making decisions and dynamically leave the colony without warning [48].…”
Section: Edge and Fog Computingmentioning
confidence: 99%
“…The ETSI NFV Management and Orchestration (MANO) is one of the most solid pieces of work in terms of NFV standardisation [4]. [48] have suggested that NFV should be the starting point for new standardisation efforts beyond NFV, given the need to define, for each application domain, the scope, properties, and requirements of service orchestration concepts is not different in the Fog Computing environment. This suggestion has also been followed by project Tacker in an attempt to integrate a MANO-compliant orchestrator on top of one of the most widely-used cloud management suites, OpenStack 3 .…”
Section: Current Standardisation Effortsmentioning
confidence: 99%
See 1 more Smart Citation
“…deployment, migration, application of policies) the Orchestrator interacts with the Cloudlets in the environment. However, due to the degree of heterogeneity of the Cloudlets in relation to the security aspects, new challenges arise when carrying out this interaction [98]. The interaction between the Orchestrator and each Cloudlet follows the steps described in the well-known Authentication, Access, and Account (AAA) framework.…”
Section: Authentication Access and Accountmentioning
confidence: 99%
“…The Service Orchestrator Architecture for Fog-enable Infrastructure (SOAFI) is a reference architecture proposed by Brito et al [98]. The development of this architecture was performed to demonstrate the importance of the Orchestrator in a Fog environment.…”
Section: Soafimentioning
confidence: 99%